KARAKTERISTIK PETANI MISKIN DAN PERSEPSINYA TERHADAP PROGRAM JARING PENGAMAN SOSIAL DI PROPINSI JAWA TIMUR - ROOSGANDHA E.M.; VALERIANA DARWIS (SOCA: Jurnal Sosial Ekonomi Pertanian, 2003)
One of the economic crisis impacts was the increasing of poverty population inIndonesia, according to the BPS data in last year of 1998 the poverty in habitant wasabout 49,5 milions people. To minimize the growth of poverty, the government haslaunched Social Safety Net ( SSN ) Program. This article was to identify whatcharacteristics that stick of the poor family and how their perception on the SSNProgram. The survey was carried out on 160 respondents in two regencies in EastJava. The survey result showed of the poor family members were low educationallevel and they were dominantly engaged in agricultural sector. In participating withthe SSN program, their mostly conducted whatever the government told, becausethey didn’t know much about the program afterall. Eventhough there were severalweaknesses, but they still enjoyed out could and hoped the program would besustained.